2012
DOI: 10.1074/jbc.m111.318410
|View full text |Cite
|
Sign up to set email alerts
|

T7 RNA Polymerases Backed up by Covalently Trapped Proteins Catalyze Highly Error Prone Transcription

Abstract: Background: Proteins are often covalently trapped on DNA by DNA damaging agents, forming DNA-protein cross-links (DPCs). Results: T7 RNA polymerases back up by DPCs and generate extensive mutations upstream of DPCs. Conclusion: Backed up T7 RNA polymerases catalyze damage-independent highly error prone transcription. Significance: Transcriptional fidelity may differ significantly between smoothly traveling and roadblocked RNA polymerases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 46 publications
0
44
2
Order By: Relevance
“…It has been shown that DPCs impede the progression of the UvrD helicase involved in nucleotide excision repair only when placed on the translocating strand (14). The progression of T7 RNA polymerase that transiently disrupts dsDNA for transcription is also blocked by DPCs only when DPCs are placed on the transcribed strand (17). It follows that replicative helicases (DnaB, T7gp4, Mcm467, and Tag), UvrD helicase, and T7 RNA polymerase are blocked by DPCs on the translocating or transcribed strand, but not by those on the nontranslocating or nontranscribed strand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that DPCs impede the progression of the UvrD helicase involved in nucleotide excision repair only when placed on the translocating strand (14). The progression of T7 RNA polymerase that transiently disrupts dsDNA for transcription is also blocked by DPCs only when DPCs are placed on the transcribed strand (17). It follows that replicative helicases (DnaB, T7gp4, Mcm467, and Tag), UvrD helicase, and T7 RNA polymerase are blocked by DPCs on the translocating or transcribed strand, but not by those on the nontranslocating or nontranscribed strand.…”
Section: Discussionmentioning
confidence: 99%
“…Forked DNA substrates containing DPCs for helicase assays (Fig. 1B) were constructed using methods similar to those described previously (13,17,(43)(44)(45). Briefly, a 25-mer oligonucleotide containing oxanine was ligated enzymatically with dT 60 or dT 40 using a scaffold DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to their exceptional bulkiness, DPCs are expected to interfere with essential DNA transactions such as transcription and replication (for methods that detect DPCs, see Supplementary information S1 (figure)). Indeed, DPCs form strong blocks for transcription by RNA polymerases when located on the transcribed strand 22 . Furthermore, DPCs (and DPC-mimicking biotin-streptavidin adducts) have been shown to inhibit the unwinding of the DNA duplex during replication in vitro 23,24 and, consequently, to interfere with replicationfork progression in vivo 25 .…”
Section: Toxicity and Effects Of Dpcsmentioning
confidence: 99%
“…azadC is incorporated into DNA and covalently traps the reaction intermediate of DNA cytosine methyltransferase, giving rise to DNA-protein cross-links (DPCs) [31]. DPCs block DNA replication and transcription [32,33] and hence constitute the major lethal lesions upon treatment with azadC. cisPt is a bifunctional DNA-damaging The treated cells were further incubated in fresh medium for 6 days, and colonies were scored to calculate the surviving fraction.…”
Section: Discussionmentioning
confidence: 99%